The design of interdigital bandpass filter on metamaterial substrate / Nor Atiqah Che Mohd Din - Che Mohd Din, Nor Atiqah (2009)
Nowadays, the world telecommunication become more complex and need a high frequency in transferring information. There are also increasing demands for the development of miniaturized and high performance microwave components such as filters to meet the emerging telecommunication applications. Therefore, many designers have recently concerned and developed to reduce the volume, weight as well as mass production cost. This project focuses a new invention of multilayer bandpass filter that consist of metamaterial as the substrate. The presence of metamaterial as a new composite and artificial dielectric gives good results in terms of the return and insertion losses as well as stopband attenuation. An S-structure with combinations of Flame Retardant 4 (FR-4) and Perfect Electric Conductor (PEC) has successfully performed metamaterial. The metamaterial behaviors are only viable at certain frequency and for certain design. A lot of effort has been done to prove that the design structure follows the metamaterial behavior. Based on simulated result, the return loss of metamaterial bandpass filter is two times better performance than conventional bandpass filter. At center frequency, the insertion loss and stopband attenuation for metamaterial bandpass filter have been improved about 58.6% and 14.2% respectively as compared to the conventional bandpass filter. As for Voltage Standing Wave Ratio (VSWR), metamaterial bandpass filter provides 49.7% better performance than the conventional one.